2020
DOI: 10.1038/s41598-020-72032-4
|View full text |Cite
|
Sign up to set email alerts
|

Host phylogeny and life history stage shape the gut microbiome in dwarf (Kogia sima) and pygmy (Kogia breviceps) sperm whales

Abstract: Gut microbiomes perform crucial roles in host health and development, but few studies have explored cetacean microbiomes especially deep divers. We characterized the gut microbiomes of stranded dwarf (Kogia sima) and pygmy (K. breviceps) sperm whales to examine the effects of phylogeny and life stage on microbiome composition and diversity. 16S rRNA gene sequence analysis revealed diverse gut communities (averaging 674 OTUs) dominated by a few symbiont taxa (25 OTUs accounted for 64% of total relative abundanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 63 publications
2
10
0
Order By: Relevance
“…Among marine mammals, which differ in their gut microbiota compared to terrestrial relatives (Nelson et al, 2013a ), the majority of studies indicate that the microbiota is not strongly influenced by host sex. Studies in leopard seals ( Hydrurga leptonyx (Blainville, 1820)) (Nelson et al, 2013b ), dugongs ( Dugong dugon (Müller, 1776)) (Eigeland, 2012 ), manatees ( Trichechus manatus Linnaeus, 1758) (Merson et al, 2014 ), bottle nose dolphins ( Tursiops truncatus (Montagu, 1821)) (Bik et al, 2016 ), and kogiid whales ( Kogia sima (Owen 1866) & Kogia breviceps (de Blainville, 1838)) (Erwin et al, 2017 ; Denison et al, 2020 ) have all not found a significant association between host sex and gut microbiota. By contrast, elephant seals ( Mirounga leonina (Linnaeus, 1758)) do exhibit pronounced differences in the microbial communities of males and females.…”
Section: Sexual Differences In the Microbiota Of Aquatic Animalsmentioning
confidence: 99%
“…Among marine mammals, which differ in their gut microbiota compared to terrestrial relatives (Nelson et al, 2013a ), the majority of studies indicate that the microbiota is not strongly influenced by host sex. Studies in leopard seals ( Hydrurga leptonyx (Blainville, 1820)) (Nelson et al, 2013b ), dugongs ( Dugong dugon (Müller, 1776)) (Eigeland, 2012 ), manatees ( Trichechus manatus Linnaeus, 1758) (Merson et al, 2014 ), bottle nose dolphins ( Tursiops truncatus (Montagu, 1821)) (Bik et al, 2016 ), and kogiid whales ( Kogia sima (Owen 1866) & Kogia breviceps (de Blainville, 1838)) (Erwin et al, 2017 ; Denison et al, 2020 ) have all not found a significant association between host sex and gut microbiota. By contrast, elephant seals ( Mirounga leonina (Linnaeus, 1758)) do exhibit pronounced differences in the microbial communities of males and females.…”
Section: Sexual Differences In the Microbiota Of Aquatic Animalsmentioning
confidence: 99%
“…The coupling of the eukaryotic host and its respective microbial communities ("microbiome") has been reclassified as a meta-organism, representing the mutualistic dependence between a multicellular organism and its respective microbial communities 1 . Factors such as host age 2 , life history 3 , diet 4,5 , environment 6,7 , and body site 8 contribute to the composition of microbial communities to varying extents, both internally (e.g., oral, gut, reproductive tracts, etc.) and externally (integumentary system, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations have focused on characterizing the microbiomes of marine mammals to gain new insights into their roles in host biology , ecology , and evolution (e.g. Apprill et al 2014, Nelson et al 2015, Erwin et al 2017, Godoy-Vitorino et al 2017, Nishida and Ochman 2018, Suzuki et al 2019, Apprill et al 2020, Centelleghe et al 2020, Denison et al 2020, Robles-Mala gamba et al 2020. Micr obiome c har acterization has also been identified as an important tool for monitoring the health of marine mammals in a r a pidl y c hanging ocean envir onment (r eview ed b y Nelson et al 2015, Apprill 2017.…”
Section: Introductionmentioning
confidence: 99%